Metode Pembelajaran Role Playing dalam Meningkatkan Keaktifan dan Hasil Belajar IPA Pada Materi Pertumbuhan Makhluk Hidup - JUMINTEN, BERNADETA; SIREGAR, TIURLINA (Jurnal Ilmu Pendidikan Indonesia, 2019)
The purpose of this study was to determine the increase in activeness and learning outcomes of students by using role playing learning methods in mahkul living growth material at SD YPPK St. Peter Nabire. The method used is quasi perimental. The results of the study increased the learning activeness of science in the material of growth of living creatures by 44.4% and n-Gain on average by using role playing learning methods of 0.9 with a high category. Learning outcomes after learning by using the role playing method in class VI of SD YPPK St. Peter.